CCAFS Knowledge by the Numbers 2018 - Abreu, David; Ramírez, Margarita M.; Epp, Marissa van (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
We are pleased to share with you the stats and analysis of CCAFS' knowledge and data sharing achievements in 2018.